THE PREVALENCE OF PERI-IMPLANTITIS IN PATIENTS WITH OBESITY. A REVIEW OF LITERATURE - Mihaela Butnaru; Dora Popescu; Mihaela Tanase; Dorin Nicolae Gheorghe; Cristian Arsenie; Valentin Barbu; Maria Alexandra Martu; Ion Rogoveanu; Petra Surlin (Romanian Society of Oral Rehabilitation, 2019)
Obesity is a chronic , complex, multifactorial disease, which develops as a result of the interaction between genotype and life style. Up to now has not been fully elucidated the mechanism by which it occurs and is developing obesity, but it has been noted that it involves both social factors, as well as those cultural, behavioural, physiological, metabolic, and genetic. The aim of this review is to evaluate how different sistemic diseases, beside type 2 diabetes,smoking , obesity may be risk factors in the onset of perimplantitis. The association between periodontal disease and obesity has been shown in several studies to different age groups. Excessive adipose tissue produces a reduced inflammation which is a cause of oral amendments. In obesity was noticed this inflammation which can be a point of contact between this and periodontal disease or periimplantitis disease.